HANDWASHING BEHAVIOR, SNACK EATING HABITS AND E.COLI CONTAMINATION WITH DIARRHEA IN ELEMENTARY SCHOOL STUDENTS IN TANJUNGPINANG CITY AND CIMAHI CITY - Luh Pitriyanti; Yosephina Ardiani Septiati; Annisa Pratiwi Putri; Mimin Karmini (Bajang Institute, 2023)
Diarrhea is an endemic disease that has the potential to cause pandemic and is still a contributor to the mortality rate in Indonesia. The behavior of elementary school students in choosing snacks and hand washing with soap is often the cause of diarrhea. The purpose of this study was to determine the relationship between the habit of consuming snacks, hand washing behavior and E.coli contamination in snacks with the incidence of diarrhea in public elementary school students in Tanjungpinang and Cimahi, Indonesia. This study was a cross sectional design. The population in this study were all public primary school students in grades 4, 5 and 6 from 15 public primary schools in Bukit Bestari sub-district and 18 public primary schools in Cimahi Utara sub-district. Sampling was conducted using quota sampling method (30 students per school) so that the minimum number of samples reached 990 students. Based on the results of data analysis, it can be concluded that there is no relationship between hand washing and diarrhea in elementary school students. There is a relationship between the habit of eating snacks and consumption of snacks containing E.coli with the incidence of diarrhea in elementary school students